Komunikasi Islami sebagai Pilar Silaturahmi: Kajian Berbasis Hadis - Fajri Chairawati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study aims to analyze the principles of Islamic communication based on hadith and its implications in maintaining harmonious social relations. Using a qualitative method based on library research, by reviewing literature, journals, and research reports. The results show that Islamic communication is based on the principles of honesty, gentleness, empathy, and good manners. The implementation of Islamic communication includes the habit of giving greetings, speaking politely, visiting the sick, and attending invitations and funerals as a form of respect and social solidarity. This research also reveals the challenges in implementing Islamic communication in the modern era, such as the influence of social media, lack of awareness of speech etiquette, and an increasingly individualistic lifestyle. By understanding and applying Islamic communication consistently, it is hoped that more harmonious social relations can be realized, both in the family and the wider community.